MAVENDI (MAGNETIC VENN DIAGRAM): MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KEAKTIFAN SISWA DI ERA NORMAL BARU - Wasilatul Murtafiah; Siti Namiroh; Darmadi Darmadi; Ika Krisdiana; Titin Masfingatin (Prodi Pendidikan Matematika FKIP Universitas Madura, 2020)
With the COVID-19 pandemic, the government has decided to get used to life with a new normal era. Education in the new normal era certainly requires new adjustments to the organization of learning including the provision of learning media. Magnetic Venn Diagrams (MAVENDI) are designed as learning media to increase student activity on the set material. The purpose of this study was to determine the results of the development of MAVENDI to improve student learning activities in the new normal era on the set material. The method used is research and development (R&D) with the 4D model which is focused on the development stage. A limited trial was conducted on 6 students and a field trial on 12 VII grade students of Singo Walisongo Magetan, East Java. Data collection using a validation questionnaire sheet, questionnaire responses and observations of student activity. The results of the development of this media were declared to be quite valid with a percentage of 88.59% based on an expert validation questionnaire, this media obtained high practicality criteria with a final score on a limited trial of P = 4.23 and on a field trial of P = 4.23 based on student response questionnaire. This media was declared effective by obtaining a percentage of 66.7% in limited trials, whereas in field trials obtained 64.7% with active criteria, based on observations of student activity.